Особливості грошового обігу Галичини та Буковини в часи російської окупації періоду Першої світової війни - Орлик, С. В.; Orlyk, S. (Ośrodek Badań Europy Środkowo-Wschodniej, 2018)
У статті розглянуто Львівські та Чернівецькі бони періоду російської окупації під час Першої світової війни: особливості та обставини випуску. Звернуто увагу на дозвільну процедуру випуску міських бон на окупованих територіях. Відмічено, що цей процес не набув масового характеру і блокувався з боку російської окупаційної влади, оскільки паралельне існування австрійської валюти та сурогатних грошей не сприяло безперешкодному введенню російської валюти на окупованих територіях. По суті російська окупаційна влада була противником випуску будь-яких сурогатних грошей, і лише обставини (зокрема, відвідини міста Львова Миколою ІІ 9 квітня 1915 р.) деякою мірою сприяли позитивному вирішенню цієї проблеми, виключно для одного міста Львова. During the First World War when the Russian troops occupied the territory of Galicia and Bukovina the cities and towns of these regions were in a difficult financial situation. The issue of urban bank notes aimed at solving the problem of lack of exchange coins and the temporary solution of financial issues of the cities of Galicia and Bukovina. The article deals with the Lviv and Chernivtsi bank notes of the period of Russian occupation during the First World War: peculiarities and circumstances of the issue. Attention is drawn to the permitting procedure for the issue of urban bank notes in the occupied territories. It was noted that this process was not massive and was blocked by the Russian occupation authorities since the parallel existence of the Austrian currency and surrogate money did not contribute to the unrestricted introduction of the Russian currency in the occupied territories. Actually, the Russian occupation authorities were opposed to the issuance of any surrogate money and only circumstances (in particular, the visit of the city of Lviv by Nicholas II on April 9, 1915) contributed to the positive resolution of this problem to a certain extent only for one city of Lviv.
Specificity of money circulation in Galicia and Bukovina at the time of russian occupation during the first world war
Keywords: Галичина; Буковина; Перша світова війна; бона; російська окупація; "розмінна криза"; Galicia; Russian occupation; World War I; Halychyna; financial policy; coin